Penerapan Media Gemini AI (Artificial Intelligence) Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih - Khairunnisa; Zulhijra; M. Robbani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aims to examine the effect of using Gemini AI as a learning medium on students’ learning outcomes in Fiqh subjects. The research employed a quantitative approach with a one-group pretest-posttest design involving 37 students as the sample. Data were collected through multiple-choice tests administered before and after the use of Gemini AI. The results showed a significant improvement in learning outcomes, with the average score increasing from 75 to 86 and the percentage of students meeting the minimum mastery criteria rising from 45.9% to 81.1%. Data analysis using SPSS version 25 revealed a significance value of 0.000 (<0.05), indicating that Gemini AI positively influences students’ learning achievement. The use of this media created an interactive and engaging learning atmosphere, motivating students to be more active in the learning process. These findings suggest that Gemini AI can be an effective alternative learning tool to improve the quality of learning and support the integration of technology in Islamic education.